Leveraging data as a patient-scientist: frustrations and opportunities - Sáez Rodríguez, Julio (Nature reviews. Nephrology, 2025)
The transition from data scientist to patient-scientist has given me new perspectives into clinical research and strengthened my commitment to open science. Although limitations on data availability have led to frustration, collaboration bodes well for a future in which patients will have access to more personalized information.